Silicon Polymers - Muzafarov, Aziz M. (Advances in Polymer Science, 2011)
Modern Synthetic and Application Aspects of Polysilanes: An Underestimated Class of Materials?, by A. Feigl, A. Bockholt, J. Weis, and B. Rieger; * Conjugated Organosilicon Materials for Organic Electronics and Photonics, by Sergei A. Ponomarenko and Stephan Kirchmeyer; * Polycarbosilanes Based on Silicon-Carbon Cyclic Monomers, by E.Sh. Finkelshtein, N.V. Ushakov, and M.L. Gringolts; * New Synthetic Strategies for Structured Silicones Using B(C6F5)3, by Michael A. Brook, John B. Grande, and François Ganachaud; * Polyhedral Oligomeric Silsesquioxanes with Controlled Structure: Formation and Application in New Si-Based Polymer Systems, by Yusuke Kawakami, Yuriko Kakihana, Akio Miyazato, Seiji Tateyama, and Md. Asadul Hoque;.